Efektivitas Iklan Pajak Di Rakyat Bengkulu Televisi Dalam Membangun Kesadaran Masyarakat Membayar Pajak - Rian Renaldo; Vethy Octaviani; Antonio Imanda (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
This study aims to determine the effectiveness of advertising tax in Bengkulu People Television in building public awareness of the tax are used as inputs Revenue Service through Samsat Bengkulu Province, Bengkulu City. This study is used to further socialization strategy. This study is a quantitative survey research using descriptive analysis dimensions CRI Awareness, Comprehed (Comprehension), Interest, Intentions, and Action. The data used in this paper, Questionnaire, Observation, Documentation. This research uses 100 respondents. Charateristics or profile of respondents were asked to the respondents is about sex, and age based on the characteristics of sex, most respondents were males by 60%, this shows that the percentage of males is higher than the percentage of women. Based on calculation CRI Awareness, Comprehed (Comprehension), Interest, Intentions, and Action, the obtained value by 71% thus, it can be concluded that the effectiveness of advertising tax in RBTV in building public awareness paying taxes reach effective level